Influence of Lexical Development on Reading and Spelling Skills: Effects of Enhancement on Second-Grade Children in Primary School - Oriana Incognito; Alice Mercugliano; Lucia Bigozzi (MDPI AG, 2023)
Previous studies suggest that lexical competence is an important factor that influences reading skills and spelling accuracy in primary school children. Understanding the relationship between these skills will provide valuable insights to improve reading and writing enhancement and intervention strategies. The aim of this pre-post longitudinal study is to examine the effectiveness of an enhancement program, in which there are activities proposed through a narrative and metacognitive methodology, designed to develop the cognitive processes of lexical acquisition and its effects on reading and writing ability. A total of 74 primary school children (M-age = 7.04 years) participated in the research. They were divided into groups: experimental, which carried out the enhancement, and control groups, which carried out the typical school program. The results show that children who carried out the enhancement obtained higher scores in reading skills, specifically in reading accuracy and text comprehension and spelling accuracy, in comparison with their peers in the control group. These results suggest that strengthening the lexical semantic pathway, as theorized by Coltheart's two-way model, can lead to improved reading comprehension and diminished reading errors and spelling inaccuracies.